Sumbangan dan prospek sektor perindustrian dalam ekonomi Malaysia :perkembangan dan perbandingan industri makanan dengan industri perkilangan di Sarawak - Mohamad Sharkawi, Abdul Aziz (Universiti Malaysia Sarawak, 2003)
The Food Industry nowadays plays an important role in the economic development in Sarawak. The growth was influence by the high demand of food in the state due to the increasing of Sarawakian population. In order to overcome the problem, the Sarawak government has imported food from Peninsular, Sabah and overseas. With the existence of the food industry, will help to reduce the government expenditure in importing food. Furthermore, the food industry will be one of the industries that will generate more income into the Gross Domestic Product. In order to prove that all the variable taken able to influence the Gross Domestic Production and its contribution, there are some test have been done.